PENGGUNAAN PENDEKATAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN KEMAMPUAN PENGHITUNGAN PECAHAN DI SDN 01 WANAREJAN PEMALANG - Diah Susilowati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTEfforts to improve and improve the quality of education in Indonesia have longbeen carried out, including the quality of mathematics education in elementary schools.However, these efforts have not shown satisfactory results. The low achievement ofstudent achievement is due to learning that involves students actively not beingimplemented. Conventional learning that has been carried out until now, teachersdominate learning so much that student involvement in the learning process is stilllacking. In conventional learning, students are no longer the subject of learning but theobject of learning. The initial reflection on the level of students' understanding of theconcept of calculating fractions of class V in SDN 01 Wanarejan Pemalang was still lowwhen compared to other mathematical concepts, this is evidenced by the low averagevalue of the results of the daily calculation of fraction counting concepts, where studentswho get grades under the Minimum completeness Criteria there are still 73.9%, and theclass average is only 57.65 still far below the national completeness limit. This studyapplies learning activities using the STAD type Cooperative Approach. In cycle I andcycle II, the improvement in learning the concept of fraction calculation has succeededin increasing students' affective value in the components of discussion activity, questionactiveness, and question answering activity. The results of the assessment of cognitiveaspects also occurred a significant increase from the initial average value of 57.65 to67.09 in the first cycle and 70.22 in the second cycle. And when viewed from thepercentage of completeness also an increase from 26.1% to 69.6% in the first cycle and87.0% in the second cycle.Keywords: cooperative approach, STAD, fraction calculation.